The slow demise of the long-lived SN 2005ip. Issue 1 (11th August 2020) - Fox, Ori D; Fransson, Claes; Smith, Nathan; Andrews, Jennifer; Azalee Bostroem, K; Brink, Thomas G; Bradley Cenko, S; Clayton, Geoffrey C; Filippenko, Alexei V; Fong, Wen-fai; Gallagher, Joseph S; Kelly, Patrick L; et al.
ABSTRACT: The Type IIn supernova (SN IIn) 2005ip is one of the most well-studied and long-lasting examples of an SN interacting with its circumstellar environment. The optical light curve plateaued at a nearly constant level for more than five years, suggesting ongoing shock interaction with an extended and clumpy circumstellar medium (CSM). Here, we present continued observations of the SN from ∼1000 to 5000 d post-explosion at all wavelengths, including X-ray, ultraviolet, near-infrared (NIR), and mid-infrared. The UV spectra probe the pre-explosion mass loss and show evidence for CNO processing. From the bolometric light curve, we find that the total radiated energy is in excess of 10 50 erg, the progenitor star's pre-explosion mass-loss rate was 1 × 10^-2 M_ yr^-1, and the total mass lost shortly before explosion was 1 M_, though the mass lost could have been considerably larger depending on the efficiency for the conversion of kinetic energy to radiation. The ultraviolet through NIR spectrum is characterized by two high-density components, one with narrow high-ionization lines, and one with broader low-ionization H i, He i, [O i ], Mg ii, and Fe ii lines. The rich Fe ii spectrum is strongly affected by Lyα fluorescence, consistent with spectral modelling. Both the Balmer and He i lines indicate a decreasing CSM density during the late interaction period. We find similarities to SN 1988Z, which shows a comparable change in spectrum at around the same time during its very slow decline. These results suggest that, at long last, the shock interaction in SN 2005ip may finally be on the decline.